A P2P Trust Model Based on Multi-Dimensional Trust Evaluation - Wang, Xinsheng; Liang, Peng; Ma, Huidong; Xing, Dan; Wang, Baozong (Bio-Inspired Computational Intelligence and Applications, 2007)
The current P2P trust models suffer much from dishonest feedbacks and the trust metrics depending on subjective judgment excessively results in rough trust value. So this paper proposes a versatile trust model based on multi-dimensional trust evaluation, MDTrust. The concept of multi-dimensional trust is introduced and the approach of evaluation which uses the joint of subjective and objective evaluation is presented. We use the discrete degree of the set of evaluation similarity between peers’ evaluation to measure the feedback credibility, in order to resolve the problem of collusion and bad-mouthing. Consequently, simulation and analysis shows that MDTrust can calculate the trust value effectively and reasonably and discard the malicious peers from P2P system.